Educational testing and measurement classroom application and practice - Kubiszyn, Tom (Wiley, 2010)
Introduces students to the dramatic developments that have occurred in the field over the last few years. Details the US national policy changes that have fostered the ongoing, dramatic and controversial changes in general education and special education testing and assessment practices.